Μοντέλα Αξιοπιστίας σε Λογισμικά Συστήματα - Αναστοπούλου, Δήμητρα-Ίριδα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
The subject of this thesis is the usage of various mathematical models to measure the reliability of software systems.Software Engineering is the science that encompasses the description, the constructionand the maintenance of software systems.Software systems are characterised by quality, automation, productivity and minimal production and maintenance costs. It is often the case that software systems require modifications in the code of their components